К вопросу создания маневровых электровозов - Рябов, Евгений Сергеевич (Українська державна академія залізничного транспорту, 2015)
Рассмотрены вопросы создания специализированных маневровых электровозов. Проведен анализ конструкций аналогичных локомотивов, выявлены их особенности. Выполнены предварительные расчеты параметров маневровых электровозов для работы с различными категориями поездов, проанализированы результаты проведенных расчетов. Отмечено, что тяговый привод маневрового электровоза должен строиться на основе бесколлекторных машин, при этом для обеспечения работоспособности на неэлектрифицированных путях в тяговый привод должны входить дизель-генератор или накопитель энергии.

The problems of creating specialized shunting locomotives have been considered. It is noted that this kind of locomotives is successfully applied on the railways all over the world. The analysis of the structures of similar locomotives has been conducted, and their features, advantages and disadvantages have been determined. The preliminary calculations of the technical parameters of shunting locomotives for various categories of trains on the railways of Ukraine have been performed; the results of the calculations have been analyzed. It is noted that electric traction drive of a shunting electric locomotive should be based on commutatorless machines, for this purpose to ensure efficiency on non-electrified routes, traction drive should include a diesel generator or energy storage unit. Traction drive equipment must be unified and work permit from the contact network of different kinds of power, with the definition of specific circuit solutions is performed taking into account the actual operating conditions of shunting locomotive.
Revisiting the creation of an electric shunting locomotive
Keywords: маневровый локомотив; поезд; касательная мощность; железнодорожная техника; локомотив; electric locomotive; train; tangential power